PENDIDIKAN TENTANG MULTIKULTURALISME DALAM CERITA PENDEK KARYA PENULIS PRIBUMI AMERIKA [EDUCATING ABOUT MULTICULTURALISM USING A SHORT STORY BY A NATIVE AMERICAN AUTHOR] - Lestari Manggong (Universitas Pelita Harapan, 2018)
This paper discusses the contribution that reading a short story written by Native American author Sherman Alexie makes in the multicultural education. The story discussed is “This is What it Means to Say Phoenix, Arizona,” which displays cultural conflicts between Native Americans and Americans within the two main characters. In the discussion, the way such cultural conflicts are presented will be highlighted in terms of representing similar situations which can be reflected by students as individuals with multicultural identities. Cultural perceptions on the story will be discussed using the concept of multiculturalism as proposed by Menand (1995) and Native American literature by Parker (2004). Students’ perceptions on multiculturalism shown in this paper are taken from the students’ papers discussing multiculturalism, which are a required final assignment for the FSIP course. This paper will then have its proposed final conclusion that in compromising multicultural identities, a strategy of tug and let loose is needed.BAHASA INDONESIA ABSTRAK: Makalah ini membahas tentang kontribusi pembacaan cerita pendek (cerpen) karya penulis pribumi Amerika, Sherman Alexie, dalam pendidikan tentang multikulturalisme bagi mahasiswa di Program Studi Sastra Inggris Universitas Padjadjaran dalam Mata Kuliah Further Studies in Prose (FSIP). Cerpen yang dibahas berjudul “This is What it Means to Say Phoenix, Arizona,” yang di dalamnya terdapat konflik kultural antara Pribumi Amerika dan Amerika dalam diri dua karakter utamanya. Dalam pembahasan akan diperlihatkan bagaimana konflik kultural tersebut merepresentasi situasi sejenis yang dapat direfleksikan oleh mahasiswa, sebagai individu yang memiliki identitas kultural yang beragam. Pandangan-pandangan kultural yang beragam dalam cerpennya akan dibahas menggunakan konsep multikulturalisme Menand (1995) dan kesusastraan pribumi Amerika oleh Parker (2004). Pandangan-pandangan mahasiswa tentang multikulturalisme yang disampaikan dalam makalah ini bersumber dari makalah mahasiswa, yang merupakan tugas akhir untuk Mata Kuliah FSIP, yang membahas cerpen tersebut. Pembahasan pada makalah ini kemudian akan mengerucut pada suatu pandangan bahwa pada akhirnya diperlukan strategi tarik-ulur dalam upaya mengompromikan keragaman identitas kultural.